A Chinese Immigrant Paradox? Low Coronary Heart Disease Incidence but Higher Short‐Term Mortality in Western‐Dwelling Chinese Immigrants: A Systematic Review and Meta‐Analysis. Issue 12 (December 2015) - Jin, Kai; Ding, Ding; Gullick, Janice; Koo, Fung; Neubeck, Lis
Abstract : Background: Chinese form a large proportion of the immigrant population in Western countries. There is evidence that Chinese immigrants experience an increased risk of coronary heart disease (CHD) after immigration in part due to cultural habits and acculturation. This is the first systematic review and meta‐analysis that aims to examine the risk of CHD in people of Chinese ethnicity living in Western countries, in comparison with whites and another major immigrant group, South Asians. Methods and Results: Literature on the incidence, mortality, and prognosis of CHD among Chinese living in Western countries was searched systematically in any language using 6 electronic databases up to December 2014. Based on the meta‐analysis, Chinese had lower incidence of CHD compared with whites (odds ratio 0.29; 95% CI: 0.24–0.34) and South Asians (odds ratio 0.37; 95% CI: 0.24–0.57) but higher short‐term mortality after first hospitalization for acute myocardial infarction compared with whites (odds ratio 1.34; 95% CI, 1.04–1.73) and South Asians (odds ratio 1.82; 95% 1.33–2.50). There was no significant difference between Chinese immigrants and whites in long‐term outcomes (mortality and recurrent events) after acute myocardial infarction. Conclusions: These findings provide an important focus for resource planning to enhance early secondary prevention of CHD to improve short‐term survival outcomes among Western‐dwelling Chinese immigrants.